Ferritin encapsulation of artificial metalloenzymes: engineering a tertiary coordination sphere for an artificial transfer hydrogenase. Issue 32 (18th July 2018) - Hestericová, Martina; Heinisch, Tillmann; Lenz, Markus; Ward, Thomas R.
Abstract : Creating a tertiary coordination sphere around a transition metal catalyst incorporated within a protein affects its catalytic turnover and enantioselectivity. Abstract : Ferritin, a naturally occuring iron-storage protein, plays an important role in nanoengineering and biomedical applications. Upon iron removal, apoferritin was shown to allow the encapsulation of an artificial transfer hydrogenase (ATHase) based on the streptavidin-biotin technology. The third coordination sphere, provided by ferritin, significantly influences the catalytic activity of an ATHase for the reduction of cyclic imines.